2022
DOI: 10.1177/1420326x211065043
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment and health risk assessment of indoor volatile organic compounds

Abstract: In extremely cold areas with long winter months and exceptionally cold weather, classrooms are inadequately ventilated, resulting in the continuous accumulation of indoor air pollutants that may endanger human health. This article uses adsorption tube sampling-thermal desorption-gas chromatography mass spectrometry to analyze the type and concentration of volatile organic compounds (VOCs) in the classroom. The source analysis and health risk assessment were performed, and the real-time concentration of total v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The ventilation time and frequency were highly deficient for rural buildings in winter, while insufficient ventilation could lead to the accumulation of indoor air pollutants, which may harm human health. 38 As shown in Figure 4(d), 80% of farmers woke up between 6:00 and 7:00 and then opened the doors or windows for ventilation. 90% of residents went to bed after 21:00.…”
Section: Questionnaire Survey Resultsmentioning
confidence: 99%
“…The ventilation time and frequency were highly deficient for rural buildings in winter, while insufficient ventilation could lead to the accumulation of indoor air pollutants, which may harm human health. 38 As shown in Figure 4(d), 80% of farmers woke up between 6:00 and 7:00 and then opened the doors or windows for ventilation. 90% of residents went to bed after 21:00.…”
Section: Questionnaire Survey Resultsmentioning
confidence: 99%
“…A source related to office floor cleaning characterized by significant fractions (>80 %) of 2-butoxyethanol was revealed by the PCA study of Campagnolo et al (2017), although the emissions from the flooring materials themselves were not excluded. The application of PCA on 25 VOCs measured inside a university classroom in China (Bai et al, 2022), revealed that four out of seven factors were associated with deodorants, cleaners and cosmetics, though it was not possible to distinctly identify each source (more than one factor was associated with the same tracer). However, the authors concluded that among VOCs detected in the classroom, PАНs originate from automobile exhaust emissions, while the main source of halogenated hydrocarbons and chlorinated hydrocarbons was the use of solvents.…”
Section: Cleaning and Consumer Productsmentioning
confidence: 99%
“…[13][14][15] Due to the merits of easy collection and high SVOC concentrations, house dust has been extensively used to assess the pollution level, human exposure and health risks of SVOC in indoor environments. [16][17][18][19][20][21][22][23][24][25] The determination of SVOC concentrations in house dust typically consists of three procedures: sampling, pretreatment and chemical analysis. 26 The sampling of house dust mainly includes two methods: (1) the vacuum-based method, in which house dust is collected by a filter (or a sampling bag sometimes) assembled in the vacuum cleaner, which is more often used in existing studies, 11,[27][28][29] and (2) the brush-based method, in which house dust is collected using a brush.…”
Section: Introductionmentioning
confidence: 99%
“…1315 Due to the merits of easy collection and high SVOC concentrations, house dust has been extensively used to assess the pollution level, human exposure and health risks of SVOC in indoor environments. 1625…”
Section: Introductionmentioning
confidence: 99%